Conformational rearrangement of the NMDA receptor amino-terminal domain during activation and allosteric modulation - Vyklicky, Vojtech; Stanley, Cherise; Habrian, Chris; Isacoff, Ehud Y (Nature communications, 2021)
N-Methyl-D-aspartate receptors (NMDARs) are ionotropic glutamate receptors essential for synaptic plasticity and memory. Receptor activation involves glycine- and glutamate-stabilized closure of the GluN1 and GluN2 subunit ligand binding domains that is allosterically regulated by the amino-terminal domain (ATD). Using single molecule fluorescence resonance energy transfer (smFRET) to monitor subunit rearrangements in real-time, we observe a stable ATD inter-dimer distance in the Apo state and test the effects of agonists and antagonists. We find that GluN1 and GluN2 have distinct gating functions. Glutamate binding to GluN2 subunits elicits two identical, sequential steps of ATD dimer separation. Glycine binding to GluN1 has no detectable effect, but unlocks the receptor for activation so that glycine and glutamate together drive an altered activation trajectory that is consistent with ATD dimer separation and rotation. We find that protons exert allosteric inhibition by suppressing the glutamate-driven ATD separation steps, and that greater ATD separation translates into greater rotation and higher open probability.
Keywords: glycin; Kinetics; HEK293 Cells; vazba proteinů; lidé; HEK293 buňky; Protein Multimerization; Models, Molecular; kyselina glutamová; Protein Conformation; Receptors, N-Methyl-D-Aspartate; molekulární modely; alosterická regulace; konformace proteinů; receptory N-methyl-D-aspartátu; Fluorescence Resonance Energy Transfer; Glycine; multimerizace proteinu; Allosteric Regulation; Microscopy, Confocal; konfokální mikroskopie; rezonanční přenos fluorescenční energie; Protein Binding; kinetika; Glutamic Acid; Humans